Diffusion weighted image documented cerebral ischemia in the postprocedural period following pipeline embolization device with shield technology treatment of unruptured intracranial aneurysms: a prospective, single center study. (26th September 2019) - Pikis, Stylianos; Mantziaris, Georgios; Mamalis, Vasileios; Barkas, Konstantinos; Tsanis, Antonios; Lyra, Stavroula; Karkoulias, Kuriakos; Petrosyan, Tigran; Archontakis, Eftychios
Abstract : Objective: Acute ischemic stroke and silent cerebral infarctions following pipeline embolization device (PED) treatment of intracranial aneurysms have been estimated to occur in 3–6% and in 50.9–90% of patients respectively. The PED with Shield technology (PED-Shield) incorporates a surface phosphorylcholine polymer to reduce the thrombogenicity of the implant. We sought to determine the incidence of diffusion weighted image (DWI) documented cerebral ischemia after PED-Shield treatment of unruptured intracranial aneurysms. Methods: This prospective study involved a single center series of consecutive patients treated for an unruptured intracranial aneurysm with the PED-Shield. All participants underwent clinical evaluation on admission, after the procedure, at discharge, and 30 days following treatment. Brain MRI was obtained within 72 hours of the procedure. Ischemic lesions identified on DWI sequences where examined as to their number, size, and location in relation to the procedure. Results: Over 12 months, 33 patients harboring 38 intracranial aneurysms were treated with the PED-Shield in 36 procedures. Neither mortality nor clinically evident ischemic events were noted in the 30 day postprocedural period. DWI documented, silent cerebral ischemia occurred in six patients (18.18%) after six procedures (16.66%). No statistically significant risk factors for postprocedural silent cerebral ischemia were identified. Conclusion: We demonstrated a reduced rate of silent cerebral infarcts following PED-Shield treatment of intracranial aneurysms than previously reported with other endovascular treatment modalities and with the previous device generations. Further research is necessary to evaluate our results and to identify methods to reduce the incidence of postprocedural cerebral ischemic events.